URINARY TRACT INFECTION IN CHILDREN UNDER 12 YEARS OLD IN GAZA CITY PEDIATRIC HOSPITALS - AHMED SM ABU SAMAHA (International Journal of Pharma and Bio Sciences, 2012)
One hundred and forty six cases (out of 439 urine samples) were identified as confirmed positive UTI cases. The prevalence rate of UTI was 33 %. Females were harbored UTI infection more frequently than males, 81.5 %, and 18.5 %, respectively. The highest infected groups were 13-36 months (35 %), and 37-72 months (33 %). The samples confirmed as positive were 82.7 % of the mid stream, 65.8 % of sterile bag, and 100 % of samples collected by catheters. The frequency of isolated uropathogens were E. coli 71.9 %, Klebsiella pneumonia 9.6 %, Proteus mirabilis 7.5 %, Pseudomonas aeruginosa 5.5 %, Staphylococcus sp 1.4 %, Acinatobacter sp 0.7 %, Enterococcus sp 0.7 %, Enterobacter sp 0.7 %, and Candida sp 2.1 %. The most effective antibiotic were imipenem 95.8 %, Amikcin 91.0 %, Ciprofloxacin 86.7 %, Ceftazidime 84 %, Cefotaxime 81.1 %, Ceftriaxone 80.4 %, Gentamycin 79.7 %, Cefuraxime 74.1 %, Nalidixic acid 67.1 %, and Nitrofurantoin 65.0. The study emphasize a significance proportion of children suffering from UTI and therefore a appropriate strategies should be implemented to increase awareness of UTI and its complications particularly in children